Synthetic hexaploid wheat contributes favorable alleles for yield and yield components in an advanced backcross winter wheat population - Pranger, Anna Leigh, author; Byrne, Pat, advisor; Haley, Scott, committee member; Pilon-Smits, Elizabeth, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: AB-QTL; drought tolerance; synthetic-derived; wheat; yield; Great Plains